Perspective on Persian Internet Memes: Exploring Multimodal Meaning Construction and Viewpoint Dynamics - Shirin Pourebrahim (نشریه پژوهش‌های زبان‌شناسی)
This paper investigates the construction of meaning in Persian Internet memes, particularly focusing on image macros—prevalent multimodal memes characterized by a fixed image paired with textual commentary. By analyzing four popular image macros that convey humorous socio-cultural messages, this study demonstrates how these bimodal (verbo-pictorial) constructions work together to generate cohesive humorous meanings and convey distinct viewpoints. The theoretical framework is grounded in Construction Grammar and Conceptual Integration Theory, two cognitive linguistics approaches that enrich the analysis. Central to this study is the concept of Discourse Viewpoint Space, which emerges in each meme and highlights the significance of perspective in meaning creation. Through qualitative examination, the research reveals that new textual elements are often woven into iterative visual materials, forming the core content of the memes. The textual components typically fulfill constructional roles, such as adverbial clauses of reason and condition, thereby shaping the inventive aspects of meaning, often presented through fictive direct speech. The humorous interpretations arise from the systematic interplay between the images and text, as well as the integration of various conceptual spaces. The phrases and images invoke frame spaces derived from shared cultural references, such as sitcoms or interviews, reflecting community familiarity. This intersubjectivity plays a crucial role in shaping meaning. Consequently, Persian image macros serve as a medium through which meme creators articulate and reconstruct their viewpoints—including ideas, emotions, and stereotypes—by harnessing diverse discursive, textual, frame metonymy spaces, and contextual information.